Nickel(II) Complex of Polyhydroxybenzaldehyde N4-Thiosemicarbazone Exhibits Anti-Inflammatory Activity by Inhibiting NF-κB Transactivation - Shawish, H.B.; Wong, W.Y.; Wong, Y.L.; Loh, S.W.; Looi, C.Y.; Hassandarvish, P.; Phan, A.Y.L.; Wong, W.F.; Wang, H.; Paterson, I.C.; Kwee, C. (Public Library of Science, 2014)
Background